Revising the used of guided note taking in mathematics classes / Muniroh Hamat, Jamal Othman and Mohd Fahmi Zahari - Hamat, Muniroh; Othman, Jamal; Zahari, Mohd Fahmi (Unit Penerbitan JSKM, 2022)
Learning mathematics in the lecture room is a process that is influenced by the role of teachers and students as individuals who are directly involved in this learning process. As an intermediary, the teacher must know where the source of information for certain knowledge is and control the mechanism to get it if students need it at any time. The students must take notes. However, there are serious problems concerning students ’ notetaking in traditional mathematics lectures. Making sense of the content later is also difficult because many students do not include the lecturer’s oral explanations in their notes. One approach to addressing these problems can be the use of guided notes: a modified version of the instructor’s notes with certain blanks the students must fill in during the lecture. The purpose of this exploratory study was to understand the potential usefulness of guided notes in mathematics courses. With guided notes, the instructor provides some type of outline of the material to be covered, but with space left for students to complete key information. The notes combine typed information, handwritten content, and graphics, but still leave room for student notes and working out example problems. Diagrams are pre-drawn, but some key numbers are left out for students to fill in during the lecture. These notes consolidate all the technical material for a lecture into a single document, and the information is organized to align with the lecture. In this study, the useful of this method been reviewed and how well they balance the efficiency offered with the need for students to actively participate in the encoding process.